Policy Problems and Progressive Solutions to Halt Increasing Social Harms on Disadvantaged Rural Communities from Current Neo-Colonial Land Grabbing Policy in Nepal: Insights and Opinions - Dhakal, Bhubaneswor; Adhikari, Kedar (Nepal Public Policy Review, 2022)
Many critical problems are intensified in rural Nepal despite the policy advice and financial support from international agencies to alleviate them. This study attempted to explain the causes and policy solutions to the problems based on secondary sources of data and the authors’ insights. It identified that international agencies involved actively in policymaking and guided the land resource management policy to result in the best benefits to the people in privileged regions and other countries. The policies ruined institutions, resource conditions, social-ecological systems, and social environments essential for sustaining mountain farming and the rural economy in the country. The destructions exacerbated emigration, farming land abandonment, indigenous farming practice loss, food insecurity, and cultural heritage degradation. Adverse impacts of the policy interventions are exposed higher in disadvantaged areas and especially in the regions of indigenous ethnic communities. Those policies have institutionally placed the communities suffering for generations and increased risks of out-breaking interethnic conflicts and national security threats on many dimensions. This study explained some pragmatic policy measures to manage the agriculture and forestry resources for community wellbeing and national security. It also demonstrated how the national expert-driven policies would be for addressing the current problems in rural areas and the holistic development of the nation.